The public committed effective dose caused by consumption of foods & foodstuffs in Ninh Thuan - Nguyen , Trong Ngo; Nguyen , Thanh Binh; Le , Nhu Sieu; Truong , Y; Nguyen , Van Phuc; Nguyen , Thi Linh; Nguyen , Dinh Tung (Nuclear Science and Technology, 2014)
Based on the data set about radionuclides concentration in foods and foodstuffs obtained from the implementation of the National Projects on “Investigation on radionuclides and toxic elements concentration in the main kinds of foods & foodstuffs of Vietnam” and “Assessment of Marine Environmental Radioactivity Status for two selected sites of Nuclear Power Plant in the near future at Ninh Thuan Province”, a calculation software of the International Commission for Radiological Protection (ICRP), the public committed effective doses (for adult only) caused by consumption of main foods & foodstuffs in the studied experimental region were estimated. In general, the committed effective doses for adult public caused by the daily intake of radionuclides of U, 232Th, 210Pb, 210Po, 226Ra, 40K, 90Sr, 137Cs and 239,240Pu are: 7.9´10-5, 4.1´10-6, 1.1´10-2, 1.7´10-1, 1.4´10-3, 1.2´10-1, 2.32´10-4, 1.9´10-4, 2.7´10-9 (mSv/year), respectively, and the contribution of U, Th series, 40K and artificial radionuclides are 61.3%, 38.6% and 0.1%, respectively.